Analysis of Character Education Through Learning Scope in Elementary School - Liansari, Vevy; Zahra, Cindy Safrina Az; Nurdiana, Ilvi; Rahma, Kharin Nur; Maulidyah, Meilia Rifki (Procedia of Social Sciences and Humanities, 2024)
This study discusses the character education of elementary school students through the scope of learning to develop an understanding of character. The main problem faced is the lack of integration and consistency in the implementation of character education in elementary schools, as well as minimal support from parents and the community. The purpose of this research is to analyze how the curriculum, learning methods, and other factors contribute to the development of student character. The research method used is a qualitative approach, with data collection techniques in the form of participatory observation, in-depth interviews, and documentation studies of the curriculum and teaching materials. The research results show that the integration of character values in the curriculum, the use of student-centered learning methods, and evaluations that consider character development can improve students' understanding and development of character. The discussion reveals that internal factors such as motivation and emotional intelligence, as well as external factors such as family, school and community environments, play an important role in forming students' character. However, obstacles such as lack of consistency in implementation and minimal parental support can hinder the effectiveness of character education. Proposed solutions include teacher training, transparent systems of rewards and consequences, and effective communication between schools and parents. In conclusion, character education in elementary schools requires strong integration in the curriculum and support from all related parties to create an environment that supports the development of positive character in students.